2015
DOI: 10.1159/000441889
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Damage in Lymphocytes of Former Uranium Processing Workers

Abstract: The frequency of cells containing micronuclei (MN) and the presence of centromeres in these MN were analyzed in lymphocytes of 98 men from Southern Bohemia. Forty-six of them had worked at the uranium processing plant ‘MAPE Mydlovary' which was closed in 1991, and 52 men were controls from the same area. FISH using human pan-centromeric chromosome paint was employed to detect centromere-positive (CEN+) and -negative (CEN-) MN. A total of 1,000 binucleated cells (BNC) per participant were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Meenakshi and Mohankumar showed that the frequency of dicentrics in radon-exposed smoker cells was found to be higher than non-smokers by factor of 3.8 [65]. Moreover the comparison of three groups: miners, workers of uranium enterprises, and a control group revealed that chromosomal aberrations were a consequence of the effect of radon, but not of uranium [66]. Disruptions to normal chromosomal arrangement represent a major contribution to carcinogenesis.…”
Section: Genetics and Epigenetic Effects Of Radonmentioning
confidence: 99%
“…Meenakshi and Mohankumar showed that the frequency of dicentrics in radon-exposed smoker cells was found to be higher than non-smokers by factor of 3.8 [65]. Moreover the comparison of three groups: miners, workers of uranium enterprises, and a control group revealed that chromosomal aberrations were a consequence of the effect of radon, but not of uranium [66]. Disruptions to normal chromosomal arrangement represent a major contribution to carcinogenesis.…”
Section: Genetics and Epigenetic Effects Of Radonmentioning
confidence: 99%
“…The issue of physical performance and physical fitness is presented in many international studies. As a rule, these researches are related to cardiovascular problems, sedentary problems, sports performance in amateur or professional athletes, issues of overweight, high blood pressure and obesity, volumes of sports training to prevent diseases or diseases of the back and spine (1,2,3,4,5). Research into motoric performance and physical fitness in Czech professional and volunteer firefighters brings a new expanding view and additional knowledge on the topic.…”
Section: Introductionmentioning
confidence: 99%
“…Наиболее интенсивное воздействие комплекса генотоксикантов на популяции человека следует ожидать при профессиональном контакте с производственными вредностями. Этот факт многократно доказан в исследованиях кластогенных эффектов у рабочих нефтехимической [2, 3], металлургической [4][5][6], теплоэнергетической [7,8], рудодобывающей [9][10][11] и других отраслей промышленности.…”
Section: Introductionunclassified